Immunohistochemical Evaluation of Chronic Endometritis by CD138, CD3 and CD20 - Sarpal, Tarunpreet Kaur; Bhagat, Ranjeev; Punia, Rajpal Singh; N, Pavithra H; Goyal, Bharti; Handa, Uma (Annals of Pathology and Laboratory Medicine, 2019)
Background: Chronic inflammation of endometrium is often clinically silent but may present as abnormal uterine bleeding, dyspareunia, infertility, leucorrhoea and sometimes urinary symptoms. The diagnosis is often rendered on histopathological examination of endometrial biopsy showing chronic inflammatory infiltrate in general and plasma cells in particular. In order to identify scant plasma cells and lymphocytes in the chronic endometritis, immunohistochemistry is increasing being used to confirm the diagnosis. Aims and objectives: To study the utility of panel of CD3, CD20 and CD 138 in the evaluation of chronic endometritis in cases of abnormal uterine bleeding and infertility and correlate the result of immunohistochemistry with routine H & E staining. Method and Material: 100 consecutive cases of abnormal uterine bleeding and infertility were taken and histopathological diagnosis was made. IHC with all the three markers were applied in all the cases irrespective of histopathological diagnosis. Results: A total of 100 cases of endometrial currettings and biopsies were studied who presented with AUB. 17 cases were diagnosed as chronic endometritis purely on histopathology while 8 additional cases were identified with help of immunohistochemistry. Two cases diagnosed on histopathology were negative on immunohistochemistry. Out of all the three markers CD 138 was the most specific while CD 3 was least specific in diagnosing chronic endometritis. Conclusion: Immunohistochemistry particularly CD 138 is very useful in suspected cases of chronic endometritis particularly in cases where histopathology does not show any evidence of chronic inflammation.